When markets fall down: are emerging markets all the same? - Ramos, S. (2015)
This paper studies the dynamics of stock market regimes in emerging markets. Using a mixture version of the standard regime-switching model, we find that the 18 analysed emerging markets can be clustered into three groups. Whereas each of these three groups is characterized by the same two regimes-a bull state with positive returns and low volatility and a bear state with negative returns and high volatility-they clearly differ with respect to their regime-switching dynamics. The first group contains stock markets which swing frequently between the two regimes, the second group shows more regime persistence, and the third group consists of stock markets that are less likely than the others to move to a bear regime period. Standard practice among stock market analysts is to group emerging markets by geographical region. The fact that our model-based clustering is only weakly related to such a regional classification demonstrates the limited validity of the latter. Moreover, a detailed analysis of regime synchronicities across the 18 studied emerging markets shows that there is evidence of regime synchronicity for certain pairs of markets, but this does not rule out that two synchronized markets have different regime dynamics and thus belong to different regime-switching clusters. Hence, our results show that it is incorrect to treat the studied emerging markets as a single homogeneous group because there is strong evidence for substantial differences in their regime-switching dynamics.